Effects of Electrolyte Beverage on Preventing Dehydration among Workers in Different Environmental Temperature - Ermita Isfandiary Ibrahim Ilyas; Saptawati Bardosono; Juwalita Surapsari; Hans-Joachim Freisleben (Indonesian Nutrition Association, 2018)
Background and ObjectivesWater and electrolyte balance is important to maintain cognitive and physical performance, especially in hot environment. This study aims to evaluate the effects of two different type of fluid intake at the workplace in preventing dehydration among male workers working in a hot and conveniently cool environment.Methods and Study DesignThis randomized double-blinded placebo controlled trial study was performed in two appointed factories in West-Java in January-February 2012. Seventy-eight healthy male subjects, age 25-45 years were selected and they were grouped based on their working environmental temperature, i.e. hot and conveniently cool environment. The subjects were randomly allocated in two intervention phases by using crossover approach, to have non-electrolyte beverage (plain water) and electrolyte drink in the workplace for 2 days, respectively. Hydration and electrolyte biomarkers were collected from blood and urine samples at before and after the intervention.Results and Conclusions:At baseline, subjects of the hot environment workplace had higher daily working hours, hemoglobin, hematocrit, blood viscosity, and blood sodium concentration as compared to those of conveniently cool environment (P<0.05). After the intervention, for the subjects in hot environment alone, there were significantly lower value of blood viscosity, hemoglobin, and hematocrit, but significantly higher value for blood sodium, USG (urine specific gravity), pH, urinary sodium, urinary potassium and urinary chloride (P<0.05), among subjects having the electrolyte drink as compared to the plain water. In conclusion, this study confirmed that consumption of electrolyte beverage during working in hot environment temperature could help improve hydration status and electrolyte concentration.